Komparace procesní úpravy správy daní v České republice a Slovenské republice - Štefánková, Stanislava (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Diplomová práce se zaměřuje na správu daní v České a Slovenské republice. Zabývá se komparací procesní úpravy správy daní, porovnává zásady obsažené v příslušných předpisech a okrajově se zabývá zásadami dobré správy. Porovnává povinnosti daňového subjektu vůči správci daně u vybraných daní. Práce obsahuje doporučený postup při řešení modelových problémových situací.

The diploma thesis focuses on tax administration in the Czech Republic and in Slovakia. It deals with the comparison of procedural law of tax administration, compares the principles enshrined in the relevant laws and marginally deals with the principles of good administration. It also compares chosen taxes obligations, which the taxpayer has to comply with towards tax authorities. The thesis also contains recommended solutions for simulated problem situations.
Comparison of Tax Procedural Law in Czech Republic and Slovak Republic
Keywords: daň; daňová povinnost; daňový subjekt; zdaňovací období; správa daně; správce daně; dobrá správa; daň z příjmu; daň z přidané hodnoty; silniční daň; tax; tax liability; taxpayer; taxation period; tax administration; tax authorities; good administration; income tax; value added tax; vehicle tax